The New Mode of Instability in Viscous High-Speed Boundary Layer Flows (Advances in Applied Mathematics and Mechanics, 2018)
The new mode of instability found by Tunney et al. [24] is studied withviscous stability theory in this article. When the high-speed boundary layer is subjectto certain values of favorable pressure gradient and wall heating, a new mode becomesunstable due to the appearance of the streamwise velocity overshoot ($U(y) > U_∞$) inthe base flow. The present study shows that under practical Reynolds numbers, thenew mode can hardly co-exist with the conventional first mode and Mack's secondmode. Due to the requirement for additional wall heating, the new mode may onlylead to laminar-turbulent transition under experimental (artificial) conditions.